2019
DOI: 10.1016/j.nicl.2019.102010
|View full text |Cite
|
Sign up to set email alerts
|

Resting state network plasticity related to picture naming in low-grade glioma patients before and after resection

Abstract: HighlightsPatients post DLGG surgery use attentional resources to compensate deficit.Functional plasticity occurs at secondary regions at distance from the lesion.Picture naming requires the integration of multiple resting-state networks.The right hemisphere plays also an important role in language processing.A whole brain approach with clinical input in case of lesion is the way forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…DLGG is a slow-growing primary brain tumor and is associated with marked functional plasticity ( 15 ). DLGG facilitates reorganization of functional networks adjacent to the tumor ( 16 18 ), resulting in increased FC ( 19 ). In our study, gliomas were located in the left temporal lobe, which is close to the visual network.…”
Section: Discussionmentioning
confidence: 99%
“…DLGG is a slow-growing primary brain tumor and is associated with marked functional plasticity ( 15 ). DLGG facilitates reorganization of functional networks adjacent to the tumor ( 16 18 ), resulting in increased FC ( 19 ). In our study, gliomas were located in the left temporal lobe, which is close to the visual network.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the language network itself, post-lesional recovery also depends on the integration and interaction of hubs not only within but also between multiple neural circuits, in agreement with the principle of variable neuro-displacement described in recovery from post-stroke aphasia [ 55 ]. Indeed, picture naming compensation relied on both the engagement of the semantic network and the fronto-parietal attentional network, as supported by an increased connectivity between the right superior parietal lobe and the right frontal operculum [ 116 ].…”
Section: Functional Compensation After Lgg Surgery: Postoperative mentioning
confidence: 99%
“…Additionally, previous studies have suggested that the alterations in functional networks may be associated with neuroplasticity in DLGG patients. For instance, van Dokkum et al reported that the right inferior parietal lobe compensated for impaired language function in DLGG patients through the reorganization of attention networks 24 .…”
Section: Discussionmentioning
confidence: 99%